Assessment of barriers for recording nursing diagnoses - Matbouei, mahsa; Mohammadi, eisa; Zargarzadeh, maryam (Advances in Nursing & Midwifery, 2015)
Abstract Background and Aim: Nursing process is a systematic approach to identify, and treat human responses to health problems and illness. Studies have showed that implementing nursing process and its steps including recording nursing diagnosis, is facing many challenges in Iran many other countries.The aim of this study was to assess nurses, and nurse managers’ point of view about the barriers for documenting the nursing diagnoses. Materials and Methods: This cross - sectional study with a problem-solving approach examined the barriers for documenting the nursing diagnosis. The study was carried out in May 2013 in Besat Nahaja, Imam Hussain (AS), and Khatamolanbya hospitals in Tehran. The sample of the study consisted of 16 nurse managers (Supervisors and matrons) and 54 nurses, and were selected by convenience sampling method. A two-part questionnaire was used for data collection. The first part of the questionnaire included demographic information and the second part was consisted of questions regarding personal, managerial and organizational barriers for identifying and recording nursing diagnoses. Each items was rated in a 5 point likert scale.Validity of the instrument was assured by face and content validity method, and reliability was determined by calculating Cronbach’s alpha reliability. Data were analyzed by SPSS software and descriptive and inferential statistics. Results: From point of view of nurses,managerial factors (2/77) were the main barriers for documentation of nursing diagnosis, while nurse managers (3/25) mentioned organizational factors as the most important barrier. Using a problem solving approach, establishing in service and continuing education programs is proposed. Conclusions: The recommended strategy for improving documentation of nursing diagnoses is establishing in-service education programs on nursing process and nursing diagnoses and nursing documentation. Keywords: Clinical Nurses, Nursing Diagnoses, Nursing Process,Barriers REFERENCES Akbari M,Shamsi A (2011). [A survey on nursing process barriers from the perspective of nurses in intensive care unit]. Iranian Journal of Crical Care Nursing 3 (4) 181-186. (Persian) Atashzadeh Shoorideh F Ashktorab T (2011). Factors influencing implementation of nursing process by nurses: A qualitative study [Abstract]. Iranian Journal of Shahrood University. Knowledge & Health . 6 (3) 16-23. (Persian) 1393 راهب ،84 هرامش ،24 هرود / 32 ناراکمه و یعوبطم اسهم Ayatollahi J (2004).[Administrative barriers in nursing process]. Shakiba.4 (7) 57-60. (Persian) Carpenito-Moyet LJ (2009). Nursing care plans and documentation: Nursing diagnosis and collaborative problems .5th edition. Philadelphia: Lippincott Williams&Wilkins. Hannifi N, Mohammadi A (2004).[The review of reasons for not accuracy record in nursing documentation]. Hayatt.21 (2)39-46. (Persian) Hasson H Arnetz JE (2009). The impact of an educational intervention on nursing staff ratings of quality of older people care: A prospective controlled intervention study. International Journal of Nursing Studies .46 (4) 470-478 Majidi F,Ghazanfari Z. (2005) Nurses views about Factors affecting implementation the nursing process. Knowledge & Health .5 (1) 65-31 (Persian) Mason C (1999).Guide to practice or load rubbish? The influence of care plans on nursing practice in five clinical areas in Northern Ireland. Journal of Advanced Nursing .29 (2) 380-387. McKenna H Ashton S Keeney S (2004).Barriers to evidence based practice in primary care: A review of literature. International Journal of Nursing Studies . 41 (4) 369-378. Mullre-Staub M, Lavin M, Needman IV,Achterberg T (2006). Nursing diagnosis, intervention &outcomes-application and impact on nursing practice: systematic review. Journal of Advanced Nursing .56 (5)514-531 Lunney M (2007), The critical need for accuracy of diagnosing human response to achieve patient safety and quality based service ACENDIO 238-239 Potter PA Perry AG (2007). Basic Nursing: Essentials for Practice.6th edition Philadelphia: Mosby Elsevier. Smeltzer S Bare BG Hinkle JL Cheever KH (2010). Brunner &Suddarth’s Textbook of Medical-Surgical Nursing .12th edition. Philadelphia: Lippincott,Williams and Wilkins Co. Taylor C (2000). Clinical problem –solving in nursing: insights from the literature. Journal of Advanced Nursing . 31 (4)842-849. Taylor C Lillis C Lemone P (2010). Fundamentals of Nursing, the Art and Science of Nursing Care .7th edition Piladelphia:Lippincott Williams &Wilkins